2002
DOI: 10.3989/scimar.2002.66n2145
|View full text |Cite
|
Sign up to set email alerts
|

How fast hake grows? A study on the Mediterranean hake (<i>Merluccius merluccius</i>, L.) comparing whole otoliths readings and length frequency distributions data

Abstract: SUMMARY:The hake (M. merluccius) is a target species of the Mediterranean trawl fleets. In this study, its growth was compared by two means: whole otolith readings and length frequency distribution analysis. Two growth hypotheses, fast and slow, were assumed using the results of otolith readings: (1) two rings were formed every year and (2) a single ring was formed every year. The monthly length distributions covered the period from 1992 to 1998, and the otoliths were obtained from monthly samplings between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 6 publications
4
10
0
Order By: Relevance
“…4) with the other studies, we see that the value of the slope for the length frequency, for similar values of L ∞ in all the studies, is approximately double that estimated by illicia. This situation is similar to that described in Mediterranean hake by García-Rodríguez and Esteban (2002), who suggested a hypothesis of "rapid growth" leading to the formation of two annual growth rings instead of one, as is usually accepted.…”
Section: Discussionsupporting
confidence: 52%
“…4) with the other studies, we see that the value of the slope for the length frequency, for similar values of L ∞ in all the studies, is approximately double that estimated by illicia. This situation is similar to that described in Mediterranean hake by García-Rodríguez and Esteban (2002), who suggested a hypothesis of "rapid growth" leading to the formation of two annual growth rings instead of one, as is usually accepted.…”
Section: Discussionsupporting
confidence: 52%
“…In the international age-reading workshop held in 2004 (ICES, 2004), the participants concluded that ageing hakes older than 3 years old was not possible with an acceptable level of precision and therefore ages estimated previously using the internationally agreed criteria were overestimated (de Pontual et al, 2006;Piñeiro et al, 2008Piñeiro et al, , 2009. Hence there is a need to make these criteria more uniform (García-Rodríguez and Esteban, 2002). In this sense, the results of recent tagging studies of European hake in the Bay of Biscay (de Pontual et al, 2003;Piñeiro et al, 2007) have questioned the accepted growth rate of this species.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the VBGF obtained by Mellon-Duval et al (2010) and García-Rodríguez and Esteban (2002) were considered to be the best representation of the FGH. Those produced by Aldebert and Carries (1989) and Levi et al (1994) were chosen as the best representation of the SGH.…”
Section: Methodsmentioning
confidence: 99%
“…Ragonese et al 2012), two opposing hypotheses are under consideration in the present study: (1) a fast-growing hypothesis (FGH), with a maximum age near 15 years (e.g. García-Rodríguez and Esteban 2002;Mellon-Duval et al 2010); and (2) a slow-growing hypothesis (SGH), with a maximum age near 30 years (e.g. Aldebert and Carries 1989;Levi et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation